Revision of the morphology, phylogenetic relationships, behaviour and diversity of the Iberian and Italian ant-like Tachydromia Meigen, 1803 (Diptera: Hybotidae) - Gonçalves, Ana Rita; Grootaert, Patrick; Andrade, Rui; Paulo, Octávio S.; Mengual, Ximo (European Journal of Taxonomy, 2021)
Phylogenetic inference, based on five molecular markers (COI, 28S, AATS, 12S, PGD), corroborates the synonymy of the flightless genera Pieltainia Arias, 1919 and Ariasella Gil, 1923 with Tachydromia Meigen, 1803. The secondary structure of the 28S rRNA gene is used for the first time in this family to align the multiple sequences. Molecular and morphological data are largely congruent for all known species of flightless Tachydromia. This paper treats ten western Mediterranean species (nine Iberian and one Italian) in detail, including the description of four new species: T. ebejeri Gonçalves, Grootaert & Andrade sp. nov., T. stenoptera Gonçalves, Grootaert & Andrade sp. nov., T. cantabrica Gonçalves, Grootaert & Andrade sp. nov. and T. nigrohirta Gonçalves, Grootaert & Andrade sp. nov. The male of Tachydromia pieltaini (Gil Collado, 1936) and the female of Tachydromia apterygon Plant & Deeming, 2006 are described for the first time, while a lectotype is assigned to Tachydromia pandellei (Séguy, 1941). A key to all non-macropterous Tachydromia is supplied. Knowledge on the geographic distribution of most species is considerably enhanced. The mating behaviour of Tachydromia semiaptera (Gil Collado, 1923) and Tachydromia iberica (Arias, 1919) is documented for the first time, and we propose a change in the definition of terms apterous and micropterous to properly accommodate the diversity of wing states in this cluster of species.